The endocannabinoid anandamide causes endothelium-dependent vasorelaxation in human mesenteric arteries - Stanley, Christopher P.; Hind, William H.; Tufarelli, Christina; O'Sullivan, Saoirse (2016)
The endocannabinoid anandamide (AEA) causes vasorelaxation in animal studies. Although circulating AEA levels are increased in many pathologies, little is known about its vascular effects in humans. The aim of this work was to characterise the effects of AEA in human arteries. Ethical approval was granted to obtain mesenteric arteries from patients (n = 31) undergoing bowel resection. Wire myography was used to probe the effects and mechanisms of action of AEA. RT‐PCR was used to confirm the presence of receptor mRNA in human aortic endothelial cells (HAECs) and intracellular signalling proteins were measured using multiplex technology. AEA caused vasorelaxation of precontracted human mesenteric arteries with an Rmax of ∼30%. A synthetic CB1 agonist (CP55940) caused greater vasorelaxation (Rmax ∼60%) while a CB2 receptor agonist (HU308) had no effect on vascular tone. AEA-induced vasorelaxation was inhibited by removing the endothelium, inhibition of nitric oxide (NO) synthase, antagonising the CB1 receptor and antagonising the proposed novel endothelial cannabinoid receptor (CBe). AEA‐induced vasorelaxation was not affected by CB2 antagonism, by depleting sensory neurotransmitters, or inhibiting cyclooxygenase activity. RT‐PCR showed CB1 but not CB2 receptors were present in HAECs, and AEA and CP55940 had similar profiles in HAECs (increased phosphorylation of JNK, NFκB, ERK, Akt, p70s6K, STAT3 and STAT5). Post hoc analysis of the data set showed that overweight patients and those taking paracetamol had reduced vasorelaxant responses to AEA. These data show that AEA causes moderate endothelium-dependent, NO-dependent vasorelaxation in human mesenteric arteries via activation of CB1 receptors.